Long-term neurological conditions: management at the interface between neurology, rehabilitation and palliative care - Turner-Stokes, Lynne (Clin Med (Lond), 2008)
Long-term neurological conditions (LTNCs) comprise a diverse set of conditions resulting from injury or disease of the nervous system that will affect an individual for life. Some 10 million people in the UK are living with a neurological condition which has a significant impact on their lives, and they make up 19% of hospital admissions. These guidelines build on the Quality Requirements in the National Service Framework for Long-term (Neurological) Conditions to explore the interaction between specialist neurology, rehabilitation and palliative care services, and how they may best work together to provide long-term support for people with LTNCs and the family members who care for them. The guidelines also provide some practical advice for other clinicians when caring for someone with an LTNC, and outline indications for specialist referral. This article provides a brief summary. Full details of the methods and literature evaluation, as well as tools for implementation, are available in the full guideline.